Comparative analysis of cytology and proteomics in anthers between cytoplasmic male sterile line and its maintainer line of peppers - Lü Xiaohan; Fang Xianping; Chai Weiguo; Ma Junping; Zhou Yifei (浙江大学学报. 农业与生命科学版)
Cytoplasmic male sterility (CMS) lines are the excellent materials for studying the cytoplasmic and nuclear cytoplasmic interaction and have important application and theoretical value for CMS research. Three-line hybrid seed production could not only reduce the trouble of manual emasculation and seed costs, but also protect the purity of hybrid seeds. Therefore, the production of hybrid seed using CMS lines has a great potential and market demand in the pepper production. With the continuous development of science and technology, proteomics has become an important tool to decipher the biological gene function and contribute to the plant breeding. Proteome analyses helped to explore the important plant genes, thus speeding up the process of plant breeding and genetics research. However, the current researchs on male sterile pepper were mostly concentrated in the physiological and biochemical indexes and the male sterile gene. The relevant report on CMS pepper protein was relatively less, and the research of sterile anther protein was even more rarely reported. Therefore, the aim of this study was to preliminarily identify the differences of cytology and proteomics involved in the peppers' anther of CMS line and its maintainer line.The anthers at six different stages were used in the experiment. At first, the paraffin sections of anthers were observed and used to study the differences between CMS line and its maintainer line from the apparent characteristics, and then SDS-PAGE was used for anther protein separation and identification. Differential protein bands separated by SDS-PAGE, and the proteome profiles of the differential protein bands were further analyzed and identified by LC-MS/MS and proteomics analysis.The results showed that pollen abortion occurred after metaphase. The main reason was that the callose surrounding the tetrad didn't disintegrate normally and the tapetum cells were excessive vacuolation. One-dimensional SDS-PAGE analysis revealed that, compared with its maintainer line, there were four fewer protein bands in CMS line. A total of 64 non-redundant proteins were identified by LC-MS/MS, including 12 unique proteins from band 1, 9 unique proteins from band 2, 21 unique proteins from band 3, 18 unique proteins from band 4, and 2 proteins from both band 1 and band 3, 1 protein from both band 2 and band 3, 1 protein from both band 3 and band 4. Among them, 24 proteins were involved in catalysis according to molecular function;20 proteins were involved in cell endometrial tissue according to cellular components; and 24 proteins were involved in the metabolic process according to biological processes.In conclusion, pepper CMS is mostly caused by pollen abortion. Pollen sterility is directly or indirectly related to abnormal tapetum and the lack of callose disintegration. After the differential proteome analysis between pepper CMS line and its maintainer line, we find that after metaphase, due to the decreased expression involving substance and energy metabolism in a part of the protein in the anther of male sterile line, the tapetum cells develop abnormally and the four separate microspores in development can not obtain matter and energy. Then pollen might be abortion. Therefore, in this study, the differential proteins identified by proteomics analysis can preliminarily explain the differences in cytology.